2004
DOI: 10.1111/j.1654-1103.2004.tb02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Do different competitive abilities of three fern species explain their different regional abundances?

Abstract: Question: Do different competitive abilities of three fern species explain their different regional abundances? Location: Estonia, Europe. Methods: The factorial pot experiment, in which single individuals of three fern species were grown in natural soil with 0, 2,4, and 8 neighbouring individuals of Deschampsia flexuosa. Results: The response patterns of different biomass fractions and morphological parameters of fern species were similar to each other. The diploid D. expansa was the most vulnerable to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Ontogenetic shifts towards lesser root growth have been observed in several species (Ledig et al 1970;Hawthorn and Cavers 1982;McConnaughay and Coleman 1999). Also, in the previous study, allocation to below-ground parts decreased with increasing neighbour density in both D. expansa and D. dilatata in conditions where no extreme shade was imposed as a treatment (Rü nk et al 2004). This shows that the usual plastic response to shading--decreased relative allocation into roots--is nevertheless present in the three fern species under observation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ontogenetic shifts towards lesser root growth have been observed in several species (Ledig et al 1970;Hawthorn and Cavers 1982;McConnaughay and Coleman 1999). Also, in the previous study, allocation to below-ground parts decreased with increasing neighbour density in both D. expansa and D. dilatata in conditions where no extreme shade was imposed as a treatment (Rü nk et al 2004). This shows that the usual plastic response to shading--decreased relative allocation into roots--is nevertheless present in the three fern species under observation.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study on relative competitive ability of three congeneric fern species with different distribution and abundance patterns in boreo-nemoral Europe--Dryopteris carthusiana, D. expansa and D. dilatata--we found that this trait did not directly explain the relative commonness/relative rarity of the three fern species (Rü nk et al 2004). There was, though, a clear difference in how each species responded to competitive stress.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Coherently with other studies on ferns (Rünk et al 2004), the low abundance of O. regalis near its distribution limits in Europe is linked to climatic factors. The annual availability of water proved to be the main climatic factor limiting at the southern edge of its distribution in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ecology of pteridophytes has been investigated much less than that of other vascular plants and few studies have analysed the causes of variation in the local abundance or rarity of particular fern species (Cinquemani Kuehn and Leopold 1993;Kelsall et al 2004;Rünk et al 2004).…”
Section: Introductionmentioning
confidence: 99%